Coordinated Generation and Transmission Expansion Planning with Energy Storage Systems to Allow High Penetration of Renewable Energy - Ahtisham Ali (329610); Supervisor: Dr. Muhammad Yousif (Islamabad : USPCAS-E, NUST, 2024)
TH-598
Keywords: MS EEP Thesis; MS Thesis